Simultaneous Quantification of Hederacoside C and α-hederin in Hedera Nepalensis K.Koch Using HPLC-UV - Thi Thuy Linh, Do; Thanh Duong, Hoang; Tuan Hiep, Nguyen; Thanh Huyen, Pham; Minh Khoi, Nguyen; Doan Long, Dinh (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 3, 2020)
This study develops a high performance liquid chromatography with ultraviolet detection (HPLC-UV) for simultaneous quantification of hederacoside C and α-hederin in Hedera nepalensis K. Koch. The method proposed in this study was validated in terms of the analytical parameters such as high repeatability, high accuracy and good sensitivity. The method was used to determine the content of hederacoside C and α-hederin in Hedera nepalensis K. Koch, which had been collected in Ha Giang, Lao Cai and Lai Chau. The study results show that the content of hederacoside C and the content of α-hederin ranged from 0.40 to 4.01% and 0.21 – 0.54% based on absolute dry mass, respectively. Keywords Hedera nepalensis K. Koch, hederacoside C, α-hederin, HPLC-UV. References [1] L. Jafri, et al, In vitro assessment of antioxidant potential and determination of polyphenolic compounds of Hedera nepalensis K. Koch, Arabian Journal of Chemistry. 10 (2017) 3699-3706. https://doi.org/10.1016/j.arabjc.2014.05.002. [2] S. Saleem, et al, Plants Fagonia cretica L, and Hedera nepalensis K. Koch contain natural compounds with potent dipeptidyl peptidase-4 (DPP-4) inhibitory activity, Journal of ethnopharmacology. 156 (2014) 26-32. https://doi.org/10.1016/j.jep.2014.08.017 [3] D.H. Bich, Medicinal plants and animals for medicine in Vietnam, Vol 1, Science and Technics Publishing House, Hanoi, 2006 (in Vietnamese). [4] National Institute Of Medicinal Materials, List of medicinal plants in Vietnam, Science and Technics Publishing House, Hanoi, 2016 (in Vietnamese). [5] L. Jafri, et al, Hedera nepalensis K. Koch: A Novel Source of Natural Cancer Chemopreventive and Anticancerous Compounds, Phytotherapy research. 30(3) (2016) 447-453. https://doi.org/10.1002/ptr.5546. [6] S. Kanwal, et al, Antioxidant, antitumor activities and phytochemical investigation of Hedera nepalensis K. Koch, an important medicinal plant from Pakistan, Pakistan Journal of Botany. 43 (2011) 85-89. [7] G. Uddin, et al, Biological screening of ethyl acetate extract of Hedera nepalensis stem, African Journal of Pharmacy and Pharmacology. 6(42) (2012) 2934-2937. https://doi.org/10.5897/AJPP12.828 [8] H. Kizu, et al, Studies on Nepalese Crude Drugs, III, On the Saponins of Hedera nepalensis K. Koch, Chemical and Pharmaceutical Bulletin. 33(8) (1985) 3324-3329. https://doi.org/0.1248/cpb.33.3324 [9] X. Tong, et al, Extraction and GC-MS Analysis of Volatile Oil from Hedera nepalensis var sinensis, Fine Chemicals. 24(6) (2007) 559-561. [10] EDQM, European Pharmacopoeia, fifth ed., Council of Europe, France, 2015. [11] N.T.H. Mai, et al, Simultaneous Quantification of Hederacoside C and α-Hederin from the Leaves of Hedera helix L. by HPLC, Journal of Medicinal Material. 21(6) (2016). (in Vietnamese). [12] L. Havlíková, et al, Rapid Determination of α-Hederin and Hederacoside C in Extracts of Hedera helix Leaves Available in the Czech Republic and Poland, Natural product communications. 10(9) (2015). https://doi.org/10.1177/1934578X1501000910 [13] M. Yu, et al, Determination of Saponins and Flavonoids in Ivy Leaf Extracts Using HPLC-DAD, Journal of Chromatographic Science. 53(4) (2014) 478-483. https://doi.org/10.1093/chromsci/bmu068. [14] EMEA, Validation of analytical procedures: text and methodology Q2 (R1), in International conference on harmonization, Geneva, Switzerland, 2005. [15] W. Horwitz, Official methods of analysis, 12 ed., Vol 1, Association of Official Analytical Chemists, Washington DC, 1975.